1999
DOI: 10.1017/s1047951100005588
|View full text |Cite
|
Sign up to set email alerts
|

Normal values of signal-averaged electrocardiographic parameters and QT dispersion in infants and children

Abstract: Ventricular late potentials, and dispersion of the QT interval, are markers for risk of ventricular arrhythmias. Normal values for these parameters are well established in adults, but may not apply for children. This study has investigated the age dependency of signal averaged electrocardiographic parameters and QT dispersion in 111 normal children aged from 5 days to 16 years. The results indicate that parameters change with age: duration of filtered QRS and low amplitude (< 40 /zV) terminal signal increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The mean values of QTd and the rate-corrected QTd in our study are found to be comparable to those reported previously for normal control groups of children (Tutar et al, 1998;Vialle et al, 1999).…”
Section: Interval and Dispersion 191supporting
confidence: 92%
“…The mean values of QTd and the rate-corrected QTd in our study are found to be comparable to those reported previously for normal control groups of children (Tutar et al, 1998;Vialle et al, 1999).…”
Section: Interval and Dispersion 191supporting
confidence: 92%
“…The 5 infants with a QTc 1450 ms after cisapride had a significant Biol Neonate 2001;80: [30][31][32][33][34] Zamora/Belli/Ferrazzini/Friedli Depolarization No significant differences were found for fQRS, LAS40, and RMS40 before and after cisapride (table 1). Using our reference normal values in infants, no ventricular late potentials were detected [24].…”
Section: Repolarizationmentioning
confidence: 90%
“…Anthropometric and clinical measurements are shown in [15][16][17][18][19][20][21][22][23][24][25][26][27][28] kg/m 2 vs 20.5 kg/m 2 , P = 0.415) were similar between the LBW group and the NBW group (Table I).…”
Section: Baseline Characteristics Biochemical Analysis and Echocardmentioning
confidence: 99%
“…11,12 Corrected QT dispersion (QTc-d) has been accepted as a physiological variability of regional ventricular repolarization, and the QT-d value of >40 ms was identified as facilitating ventricular arrhythmias. 13 Although considerable evidence has been published on P-wave indices and QT derivatives and concerning autonomic imbalance of the heart, [14][15][16] no studies have been conducted on the effects of LBW on Pw-d and QTc-d, particularly in children. Since no data are available concerning Pw-d and QTc-d in children with LBW <2,500 g at birth who were born at term, we aim to compare Pw-d and QT-d between normal birth weight (NBW) and LBW children, as well as compare echocardiographic data such as left atrial and ventricular dimensions.…”
Section: Introductionmentioning
confidence: 99%